On tuberculosis and COVID-19 co-infection. Issue 2 (20th August 2020) - Tadolini, Marina; García-García, José-María; Blanc, François-Xavier; Borisov, Sergey; Goletti, Delia; Motta, Ilaria; Codecasa, Luigi Ruffo; Tiberi, Simon; Sotgiu, Giovanni; Migliori, Giovanni Battista
In their correspondence, the authors raised two important issues, namely the possible association between tuberculosis (TB) and coronavirus disease 2019 (COVID-19) (can infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) re-activate TB?), and the effects of TB on early mortality in co-infected patients. COVID-19 may boost tuberculosis given infection and mortality, further studies are needed https://bit.ly/2Z2r5XO